(untitled) (African Journal of Biomedical Research, 2021)
The need to characterise optimum dosage of farmer preferred cheap and locally available dried clove bud (DCB), liable to induce anaesthesia to surgical stage in Clarias gariepinus brood-stocks necessitated this study. DCB was characterised for content of essential oil (CEO) and its chemical composition through hydro-distillation and gas chromatography (GC-MS) respectively. Ten random samples (5male and 5female) of C. gariepinus brooders(mean weight, 1.63±0.33kg) were immersed in 0.00 g/l (T1), 0.1g/l (T2), 0.2g/l (T3), and 0.3g/l (T4) concentrations of aqueous DCB, observed for time (minutes) to reach anaesthesia induction-IT, sedation-SeT, surgery-ST; and recovery-RT; then, survival (%) at 3weeks post-experimentation period. Data were analysed for differences and regression at P<0.05. DCB yielded 1.60% CEO; composed 52 chemicals containing 91.76% eugenol derivatives. Significantly, IT and SeT varied from 2.63±0.21min (T4) to 4.23±0.27mins (T2) and 5.73±0.22mins (T4) to 8.74±0.50mins (T2); ST occurred and was similar across T3 (13.95±1.69mins) and T4 (14.15±1.65mins); RT varied at 1.49±0.13mins post-SeT (T2) to 3.78±0.36 mins post-ST (T4), while survival was 100.00% in T1 - T4. The IT, SeT, ST, RT, and survival were similar across sexes in T2 - T4. Significantly, DCB regressed at concentration = 0.016 + 0.936 (RT) – 0.074 (SeT). DCB has low CEO but contain chemicals liable to induce surgical anaesthesia at 0.3g/l (T4) for about 4mins, without causing mortality in C. gariepinus brooders. Meanwhile, increased concentration would further extend the recovery time.